1992
DOI: 10.1021/j100188a010
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational overtone spectroscopy of pyrrole and pyrrolidine

Abstract: The gaseous near-infrared and visible absorption spectra of pyrrole and pyrrolidine have been measured for the first through fourth N-H stretch vibrational overtones and the second through fourth C-H stretch overtones. The C-H overtone features follow the simple local mode expression with anharmonicities of 53.9 f 0.5 cm-' for pyrrole and 60 f 2 cm-' for pyrrolidine. Multiple transitions observed in the N-H stretching regions indicate the presence of vibrational coupling to other vibrational modes. This assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 6 publications
0
29
0
Order By: Relevance
“…23,24,49,50,52,58 In the recent years, the emphasis was put on the study of anharmonicity and assignment of overtones and combination tones. 16,17,20,47,51 Very interestingly, despite the previous extensive investigation of the vibrational spectra of pyrrole, this molecule has not been studied by matrix isolation spectroscopy yet. The high tendency of pyrrole to aggregate is, without any doubt, the main factor responsible for the difficulty in isolating the molecule in matrixes.…”
Section: Introductionmentioning
confidence: 99%
“…23,24,49,50,52,58 In the recent years, the emphasis was put on the study of anharmonicity and assignment of overtones and combination tones. 16,17,20,47,51 Very interestingly, despite the previous extensive investigation of the vibrational spectra of pyrrole, this molecule has not been studied by matrix isolation spectroscopy yet. The high tendency of pyrrole to aggregate is, without any doubt, the main factor responsible for the difficulty in isolating the molecule in matrixes.…”
Section: Introductionmentioning
confidence: 99%
“…To get an insight into the reliability of the optimized geometries of this heterodimer at the employed level of theory, the optimized geometry parameters of the two monomeric units were compared with the available experimental data 14–19 (the complete results are available from the author upon request); the agreement of the presently applied level of theory with the experimental data is good. In the case of free pyrrole, the results from the present study are of essentially identical quality with the MP2 ones reported recently for this system 35.…”
Section: Resultsmentioning
confidence: 99%
“…All in all, studies of π‐type hydrogen bonding interaction between aromatic domains containing heteroatoms are of special importance for a number of chemical and biochemical phenomena. Because, to the best of our knowledge, no experimental data are available for the heterodimer considered in the this article, the obtained theoretical results were compared with the available data for the (pyrrole) 2 and (indole) 2 homodimers 7, 15, as well as with the data for free monomeric units 14, 16–19. Conclusions regarding experimental detection of the π‐bonded dimers are also derived that are expected to be helpful for further experimental studies.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the -C-O-Cstretching peak of the lactone ring was observed at 1245 and 1247 cm -1 in the control and treated samples, respectively [28]. Besides, the N-H bending peak of pyrrole ring C-N stretching peak of pyrazole ring present in proteins was appeared at 1151 cm -1 in the control sample [29,30]; whereas at 1118 cm -1 in the treated sample. The C-OH stretching peak of carbohydrates was observed at 1072 cm -1 in the control and 1085 cm -1 in the treated sample.…”
Section: Ft-ir Spectroscopic Analysismentioning
confidence: 99%